PENGUATAN NILAI-NIAI HUKUM ISLAM DALAM MATERI MUATAN PEMBENTUKAN HUKUM NASIONAL - Firdaus, Khairul; AM, Rusydi; Karim, Syofwan; Yunaldi, Wendra; Sriwahyuni, Sriwahyuni (STKIP Pesisir Selatan, 2025)
The values The basic values contained in Islamic Law, such as justice, welfare, and legal certainty, are very relevant in the formation of national laws that are relevant to the formation of national laws. Legal certainty, are very relevant in the formation of national law that reflects the morals and ethics of Indonesian society. Reflect the morals and ethics of Indonesian society. National law development in Indonesia is a complex process, involving various issues,interests, and expectations of society. Islamic law has an important role in national legal system as one of the recognized sources of law. However, the process of integrating Islamic law with national law faces various challenges, such as diversity of interpretation, harmonization with constitutional principles, as well as obstacles in implementation. Constitutional principles, as well as obstacles in implementation. This research uses literature method with a normative approach to examine various documents and literature related to the integration of Islamic law in the national legal system and literature related to the integration of Islamic law in the national legal system. The results The results show that Islamic law contributes significantly to shaping norms and values in national law. However, there are challenges that challenges that need to be overcome, including differences in understanding, the need for agreement between stakeholders, as well as a contextual understanding of Islamic law in the national legal system. Stakeholders, as well as a contextualized understanding of Islamic law in Indonesian society.